Unsur Sengaja pada Tanah Yang Tidak Dipergunakan Atau Dimanfaatkan dalam Perspektif Hukum Administrasi Pertanahan - Febrianto, Deddy; Putra, Prasta Rahandyanto; Basyarahil, Ramzy Muhammad; De Jesus, Marcello Alfarico; Harjo, David (JURNAL MINUTA, 2025)
Land plays a strategic role in Indonesia’s national development as both a livelihood and a constitutional mandate. However, the prevalence of abandoned land—over 99,099 hectares officially designated, and 854,662 hectares identified—raises critical legal concerns. Government Regulation No. 20 of 2021 on the Control of Abandoned Areas and Land aims to address this issue through administrative means yet introduces interpretative challenges surrounding the legal element of “intentionally” not utilizing land. This article examines the juridical interpretation of the “intent” requirement in determining whether land is deemed abandoned. The absence of a clear, objective definition of “intentionally” poses legal uncertainty and the risk of arbitrary state action that may infringe upon constitutionally protected land rights. Through normative juridical analysis, this study argues that the subjective nature of “intent” must be clarified by observable indicators, such as prolonged inaction, overgrown physical conditions, or documented administrative neglect. The research further highlights potential contradictions in implementation, including unequal treatment between state-held land and privately held plots. In conclusion, while abandoned land policies are essential for equitable agrarian reform, the state must ensure legal certainty, procedural safeguards, and proportional interpretation of "intent" to uphold agrarian justice and constitutional property rights. The paper recommends technical guidelines for determining intent and emphasizes the importance of due process before revoking land rights under the pretext of abandonment.